Cryptogenic Stroke: Cardiac Rhythm Monitoring as An Indispensable Screening Modality - Sunu Budhi Raharjo; Sarah Humaira; Lies Dina Liastuti (The Indonesian Heart Association, 2021)
The prevalence of stroke in Indonesia increased overtime. CS ranges from 15 to 40% from all ischemic strokes. Finding the etiology of ischemic stroke is important to prevent recurrence. AF is predicted as the etiology behind CS. The current recommendation only supports short period of ECG monitoring. However, studies have shown that a higher detection rate can be achieved with longer duration of monitoring. ICM, a diagnostic tool with the highest detection rate, is still considered cost-effective when the calculation takes into account the QALY gained. Digital health tools such as handheld devices and smartwatch ECG have revolutionized the screening of AF however it is still considered as pre-diagnostic and verification is needed to confirm the rhythm generated.